2015
DOI: 10.1071/wr14233
|View full text |Cite
|
Sign up to set email alerts
|

The role of the bandwidth matrix in influencing kernel home range estimates for snakes using VHF telemetry data

Abstract: Context Despite the diversity of available home range estimators, no single method performs equally well in all circumstances. It is therefore important to understand how different estimators perform for data collected under diverse conditions. Kernel density estimation is a popular approach for home range estimation. While many studies have evaluated different kernel bandwidth selectors, few studies have compared different formulations of the bandwidth matrix using wildlife telemetry data. Additionally, few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…For example, Gitzen et al () reported that the ref estimator performed poorly relative to hpi or hlscv in all instances except when the distribution had a singular peak of activity. In contrast, Bauder et al () reported that ref and hpi provided comparable estimates, which were more robust than those produced by the hlscv. Nevertheless, few studies evaluated the consistency of size estimates with <20 data points (Bauder et al, ; Gitzen et al, ; Kie, ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…For example, Gitzen et al () reported that the ref estimator performed poorly relative to hpi or hlscv in all instances except when the distribution had a singular peak of activity. In contrast, Bauder et al () reported that ref and hpi provided comparable estimates, which were more robust than those produced by the hlscv. Nevertheless, few studies evaluated the consistency of size estimates with <20 data points (Bauder et al, ; Gitzen et al, ; Kie, ).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, Bauder et al () reported that ref and hpi provided comparable estimates, which were more robust than those produced by the hlscv. Nevertheless, few studies evaluated the consistency of size estimates with <20 data points (Bauder et al, ; Gitzen et al, ; Kie, ). Given our results and because of the inconsistent results in the home‐range literature, we offer the rKIN user the option of estimating niche size and overlap with all four methods and suggest that their applicability to specific datasets be evaluated.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We chose MPC because of its known simplicity, and flexibility of shape (White andGarrot 1990, Powell 2000). Although we report fixed kernel estimates (with reference bandwidth) for comparison with other studies, we focus our discussion on MCP estimates, because of published reports of failures, or high variability of the kernel based estimations of home range, related to sample size (Hemson et al 2005, , Downs et al 2012, Signer and Balkenhol 2015, Bauder et al 2015. Furthermore, based on our field experience, we also think that kernel method over-estimated home range for our studied animals in particular.…”
Section: Estimation Of Home Range and Overlapmentioning
confidence: 99%